Evaluation of the variables that influence the enzymatic hydrolysis of Moxotó goat’s milk casein - Ferreira Lira, Tatiana Barros; Bezerra, Vilma Sobral; Silva, Flávio de Oliveira; Dias, Giselle Maria Pereira; de Lima Filho, José Luiz; Porto, Tatiana Souza; Porto, Ana Lúcia Figueiredo (Pesquisa Agropecuaria Brasileira, 2011)
The aim of this work was to evaluate the effects of temperature, pH, enzyme:substrate ratio (E:S), and reaction time on the enzymatic hydrolysis of Moxotó breed goat’s milk casein, using different proteolytic enzymes. Enzymatic hydrolysis of the capric casein was performed using trypsin, pepsin and papain. For each enzyme, two levels of the variables were used to assess their effects on the hydrolysis of casein, using a full factorial design (24). The hydrolysis products were visualized on SDS-PAGE. The best hydrolysis degree using papain were at pH 6.5, E:S of 1:150 and 5 hours of hydrolysis at 50°C (28.17%); for trypsin, at pH 8.5, E:S of 1:150 and 5 hours at 40°C (29.55%); and for pepsin, at pH 3.0, E:S of 1:100 and 5 hours at 40°C (38.27%). Capric casein hydrolysis is affected positively by pH and reaction time, using pepsin. Significant antagonistic interactions were observed between pH and E:S, with trypsine; and between pH, temperature and reaction time, with papain. Pepsin has high αs1, β e κ-casein hydrolysis efficiency, evidenced by the molar masses below 14.4 kDa of its products.